INCREASING THE EFFICIENCY OF TECHNOLOGICAL PROCESSES OF DRAWING AND ROLLING IN CONDITIONS OF RATIONAL USE OF DRY AND SEMI-LIQUID FRICTION FORCES UNDER THE INFLUENCE OF EXTERNAL VIBRATIONS - Malinovskyi, Yurii; Danylina, Halyna; Vlasenkov, Dmyro; Rybak, Dmitro; Oliinyk, Svitlana (Problems of Friction and Wear, 2024)
In modern technological processes of metal forming, such as cold rolling, rolling and drawing, a significant proportion of energy supplied to the rolling device is irretrievably lost to friction and wear, as well as giving the workpiece a given shape (or dimensions) as a result of plastic deformation. To assess the nature of friction in such machines, the types of frictional interaction between the material of the processed workpiece and the tool were determined, taking into account the influence of lubricants. As it was established, during metal pressure treatment, there is both "dry" and "semi-liquid" friction. Even in the presence of lubricant in the kinematic pair: fiber-wire billet dry friction prevails. As practice shows - the occurrence of significant friction forces and forces of tension of the workpiece is caused by the presence of multiple deformation microroughnesses in the receiving part of the fiber, at its interaction with the moving workpiece. These microroughnesses (on the workpiece) are sheared and plastically deformed by the interaction of the contacting pair. Moreover, this deformation process is accompanied by a continuous wave background in the sound range. For intensification of rolling and drawing processes it is recommended to use, by analogy with vibration metal cutting treatment, vibration rolling and drawing, by installing additional vibrators acting in the direction of rolling or drawing on the applied fibers. The proposed vibrators operate, as a rule, in the ultrasonic range. Optimization of the rolling (drawing) unit operation is carried out by selection of amplitude and frequency of additional vibration, providing the required mode of machine operation, which realizes the transition from "dry" friction between wire and die to "semi-liquid" friction. Implementation of measures on creation of additional devices for ultrasonic drawing and rolling allows to reduce energy costs of the rolling and drawing operation, as well as to increase the wear resistance of the tool.